Weight-based and Digital Payment Process Flow Design to Decrease Quarry Sand Sales Fraudulence Risk - Meita Annisa Nurhutami (Journal of Industrial Product Design Research and Studies, 2023)
Databases have risen to the level of being one of the most important corporate assets. The availability of data in a company is required to make the right profit decision. In running a business aiming to achieve high profitability, companies must recognize profitable items by making decisions that require knowledge of the supply chain, knowledge of past, present, and future buying patterns, and costs derived from data obtained from many different systems. In this study, a company running a quarry sand mining business is experiencing disproportions of the resource availability of quarry sands, operating expense, and profit. It leads to suspicion of fraudulence risk during the operations and transaction of the product. This study aims to minimize the fraudulence risk of quarry sand sales by using data re-verification and analytical techniques. The study implemented a process analysis and root-cause method using process flowcharting and fishbone diagram tools. The root causes of this issue happen during the initial data input process caused by three main factors namely machinery or equipment, people, and systems. The newly designed system utilizes a digital weighing scaling system for trucks in recording the initial data and deposit payment system based on the accurate truck final weight.